Dynamic Bayesian network modeling of fMRI: A comparison of group-analysis methods - Li, Junning; Wang, Z. Jane; Palmer, Samantha J.; McKeown, Martin J. (NeuroImage (Orlando, Fla.), 2008)
Bayesian network (BN) modeling has recently been introduced as a tool for determining the dependencies between brain regions from functional-magnetic-resonance-imaging (fMRI) data. However, studies to date have yet to explore the optimum way for meaningfully combining individually determined BN models to make group inferences. We contrasted the results from three broad approaches: the “virtual-typical- subject” (VTS) approach which pools or averages group data as if they are sampled from a single, hypothetical virtual typical subject; the “individual-structure” (IS) approach that learns a separate BN for each subject, and then finds commonality across the individual structures, and the “common-structure” (CS) approach that imposes the same network structure on the BN of every subject, but allows the parameters to differ across subjects. To explore the effects of these three approaches, we applied them to an fMRI study exploring the motor effect of L-dopa medication on ten subjects with Parkinson's disease (PD), as the profound clinical effects of this medication suggest that fMRI activation in PD subjects after medication should start approaching that of age-matched controls. We found that none of these approaches is generally superior over the others, according to Bayesian-information-criterion (BIC) scores, and that they led to considerably different group-level results. The IS approach was more sensitive to the normalization effect of the L-dopa medication on brain connectivity. However, for the more homogeneous control population, the VTS approach was superior. Group-analysis approaches should be selected carefully with consideration of both statistical and biomedical evidence.